UPAYA MENINGKATKAN PEMAHAMAN MEMBACA SISWA MENGGUNAKAN TEKNIK SKIMMING DI MI AL-KHAIRIYAH SINAR BANTEN TALANGPADANG - Muhtarom, Muhtarom; Habsah, Rexsa (STIT AL MULTAZAM, 2019)
This research was conducted with the aim to: (1) improve the process and student learning outcomes using skimming techniques in reading comprehension skills in fifth grade students of MI Al-khairiyah Sinar Banten Talangpadang, (2) describe student learning outcomes using skimming techniques in reading comprehension skills in Va MI Al-khairiyah Sinar Banten students in Talangpadang. This type of research is a quantitative study with a questionnaire, in the form of documentation and interviews to collect data while to determine the character of students using observation. The subjects of this study were 30 Va students. The data analysis technique used is inferential statistics. Based on data analysis, it was concluded that the learning outcomes (variable Y2) of students using skimming techniques (variable X) in reading comprehension skills (variable Y1) in Va MI Al-khairiyah Sinar Banten Talangpadang class students increased with a value of 0.765. Then the contribution becomes 76.5% based on the acquisition of R Square. This can be seen through the analysis of student learning outcomes through tests and questionnaires based on the significance value of 0,000 0.05, also based on the value of t_count2.411 and3.449 t_tabel2.125 (db = 30) significance level of 5%, so t_count t_table . Then Ha is accepted and H0 is rejected.